Attainable forms of intermediate dimensions - Banaji, Amlan; Rutar, Alex (Annales Fennici Mathematici, 2022)
The intermediate dimensions are a family of dimensions which interpolate between the Hausdorff and box dimensions of sets. We prove a necessary and sufficient condition for a given function \(h(θ)\) to be realized as the intermediate dimensions of a bounded subset of \(R^d\). This condition is a straightforward constraint on the Dini derivatives of \(h(θ)\), which we prove is sharp using a homogeneous Moran set construction.